The (Re)Invention of Biblical Exorcism in Contemporary Roman Catholic Discourses - Bauer, Nicole M. (Religion & theology, 2022)
Exorcism is flourishing once again in the Roman Catholic Church today. Discourse on the topic has been influenced by the publications of exorcists such as Malachi Martin and Gabriele Amorth. They claim biblical precedence and commissioning for their duties as exorcists and seek to emphasise their credentials by interacting with modern medicine. At the same time, they provide descriptions of demonic possession which surpass and even contradict the accounts found in the Gospels. We analyse the claims of modern exorcists concerning demons, those they possess, and how they are expelled, and evaluate these against the evidence in the Gospels. We discover that the narratives constructed by modern exorcists involves both a dramatisation of the supernatural that exceeds the exorcisms of Jesus, and the ‘medicalisation’ of exorcism as a means to legitimise the practice as a valid alternative or complement to modern medicine and psychology.